2020
DOI: 10.3390/rs12071075
|View full text |Cite
|
Sign up to set email alerts
|

Land Surface Temperature Retrieval for Agricultural Areas Using a Novel UAV Platform Equipped with a Thermal Infrared and Multispectral Sensor

Abstract: Land surface temperature (LST) is a fundamental parameter within the system of the Earth’s surface and atmosphere, which can be used to describe the inherent physical processes of energy and water exchange. The need for LST has been increasingly recognised in agriculture, as it affects the growth phases of crops and crop yields. However, challenges in overcoming the large discrepancies between the retrieved LST and ground truth data still exist. Precise LST measurement depends mainly on accurately deriving the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…LST and other parameters such as the normalized difference vegetation index (NDVI) or bare soil index (BSI) have been mostly studied in relation to urbanization [8,9]. Several studies have been conducted to analyze how changes in LST affect the variability of the microclimate of an area, the phenological cycle of vegetation [5,6], the agricultural production [10], and the land cover changes [11] using time series analysis of data. It has been observed that LST in subtropical and mid-latitude climates (between 30 • and 45 • latitude) is inversely proportional to the vegetation or tree cover of an area [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…LST and other parameters such as the normalized difference vegetation index (NDVI) or bare soil index (BSI) have been mostly studied in relation to urbanization [8,9]. Several studies have been conducted to analyze how changes in LST affect the variability of the microclimate of an area, the phenological cycle of vegetation [5,6], the agricultural production [10], and the land cover changes [11] using time series analysis of data. It has been observed that LST in subtropical and mid-latitude climates (between 30 • and 45 • latitude) is inversely proportional to the vegetation or tree cover of an area [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the emissivity of vegetation ranges from 0.96 to 0.99, while the emissivity of soils is around 0.98 [41,42]. The inaccuracy in emissivity can result in temperature errors of up to several degrees Celsius [43], and in this study we estimated emissivity of vegetation canopy and soil using the Normalized Difference Vegetation Index (NDVI), as proposed by [44].…”
Section: Thermal Image Calibrationmentioning
confidence: 99%
“…These changes affect the degree of absorption of solar radiation, albedo, surface temperature, evaporation rates, heat transmission to the soil, heat storage, and wind turbulence. Including responsible geo-environmental issues with different contaminants such as water, air pollution, greenhouse gas emissions, and even soil surface temperature (LST) would rise rapidly, which is projected to expose 69% of the world's population by 200 of this vulnerability (Weng et al, 2004, Weng et al, 2006, Mallick et al, 2008; United Nations, 2010; Zhang et al, 2013;Zhang et al, 2016;Pal and Ziaul, 2017;Heinemann et al, 2020). Increasing the demand for the application of modern technology to de ne, manage, and incorporate environmental and hydro-environmental geospatial data processes is, therefore, important for the overall sustainable development of any country's prerequisites.…”
Section: Introductionmentioning
confidence: 99%